2015
DOI: 10.3389/fpsyg.2015.00890
|View full text |Cite
|
Sign up to set email alerts
|

Turn-taking: a case study of early gesture and word use in answering WHERE and WHICH questions

Abstract: When young children answer questions, they do so more slowly than adults and appear to have difficulty finding the appropriate words. Because children leave gaps before they respond, it is possible that they could answer faster with gestures than with words. In this study, we compare gestural and verbal responses from one child between the ages of 1;4 and 3;5, to adult Where and Which questions, which can be answered with gestures and/or words. After extracting all adult Where and Which questions and child ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…One question raised by our study is why, if children can coordinate comprehension and production, they still often produce poorly timed conversational turns. Levinson (2016) suggested that children's poor timing may reflect difficulties that they have in producing complex language (consistent with naturalistic observations; Casillas et al, 2016;Clark & Lindsey, 2015), which is partially consistent with the present data: Here, children needed to produce only very simple yes/no answers, and their modal response times were actually strikingly similar to adults' response times. However, for us to fully understand how production difficulties constrain the development of conversational timing, it is important to test more complex responses as well as younger children.…”
Section: Discussionsupporting
confidence: 87%
“…One question raised by our study is why, if children can coordinate comprehension and production, they still often produce poorly timed conversational turns. Levinson (2016) suggested that children's poor timing may reflect difficulties that they have in producing complex language (consistent with naturalistic observations; Casillas et al, 2016;Clark & Lindsey, 2015), which is partially consistent with the present data: Here, children needed to produce only very simple yes/no answers, and their modal response times were actually strikingly similar to adults' response times. However, for us to fully understand how production difficulties constrain the development of conversational timing, it is important to test more complex responses as well as younger children.…”
Section: Discussionsupporting
confidence: 87%
“…One crucial follow-up to our proposal will be to test the relationship between response planning and turn timing more directly, with both experimental control of response complexity and analysis of variation in individual children as well as groups. For example, gestural answers to yes/no and wh- questions should require less effort than verbal responses and so should be faster (E. V. Clark & Lindsey, 2015). With respect to variation across groups, children from different cultural or socioeconomic backgrounds might arrive at adult-like timing earlier or later than reported here.…”
Section: Study 2: the Effect Of Age On Turn Timingmentioning
confidence: 99%
“…For both planning and predicting, they make use of their linguistic, world, and interpersonal knowledge (e.g. Ford & Thompson, 1996; Wells & Corrin, 2004; de Ruiter et al , 2006; Forrester, 2013; Clark & Lindsey, 2015), and greater predictability leads to more accurate timing estimations (Magyari & de Ruiter, 2012). In adjacency pairs, like question–answer pairs, the first speaker's turn makes the second speaker's turn more predictable; it projects the type of response that is needed next, and the addressee is then obligated to give his or her relevant response in the next turn (Schegloff & Sacks, 1973; Sacks, 1992; Schegloff, 2007; Heritage & Clayman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, even launching a fully specified utterance plan typically takes around 400 ms ( Ferreira, 1991 ; Wesseling and van Son, 2005 ; Piai et al, 2011 ). In order to achieve smooth transitions between their turns, interlocutors must therefore begin to plan their utterances while listening to their partner and launch them shortly before the end of the partner’s turn ( De Ruiter et al, 2006 ; Magyari and De Ruiter, 2012 ; Pickering and Garrod, 2013 ; Clark and Lindsey, 2015 ; Garrod and Pickering, 2015 ; Riest et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%